Best interests decisions: professional practices in health and social care. (24th August 2013) - Williams, Val; Boyle, Geraldine; Jepson, Marcus; Swift, Paul; Williamson, Toby; Heslop, Pauline
Abstract This paper reports on data collected in 2011 from a national study about the operation of the best interests principle, a key feature of the Mental Capacity Act (MCA) 2005 for England and Wales. The objective was to provide a picture of current professional practices in best interests decision‐making. Four contrasting sample sites were selected, in which National Health Service trusts, social care and other organisations were recruited to participate. A multimethod design was followed, including an online survey with 385 participants, followed by qualitative research through a telephone survey of 68 participants, and face‐to‐face semi‐structured interviews following up 25 best interests cases, with different perspectives on the process in 12 of those cases. The current paper reports only on the qualitative findings. The findings indicate that the MCA was successful in providing a structure for these practitioners, and that the five principles of the MCA were in general adhered to. A variety of perceived risks led to best interests processes being undertaken, and a typical scenario was for a period of hospitalisation or ill health to trigger a best interests decision process about a social care and or a life decision. The study supported previous research in finding the notion of capacity the most difficult aspect of the MCA, and it provides evidence of some specific capacity assessment practices, including problematic ones relating to 'insight'. Best interests decisions were often made by consensus, with practitioners taking on different roles within the process. Meetings played a key part, but other ways of involving people lacking capacity and significant others were also important. It was recommended that the issues highlighted in this research could be clarified further in the Code of Practice, or within risk guidance.